Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1055/s-0033-1334905
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Insulin Aspart vs. Regular Human Insulin with or without Insulin Detemir Concerning Adipozytokines and Metabolic Effects in Patients with Type 2 Diabetes Mellitus

Abstract: After stopping oral antidiabetic drugs in type 2 diabetes mellitus, insulin aspart in comparison to human regular insulin decreased effectively HbA1c levels without significant difference. Moreover, insulin aspart in comparison to human regular insulin does not have any substantial benefits concerning metabolic effects and adipocytokines in type 2 diabetes mellitus over a 24 months treatment period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 11 publications
1
4
0
Order By: Relevance
“…Our analysis showed that treating poorly controlled patients with BIAsp 30 is likely to be cost-saving and cost-effective in Iran. In parallel to the results of our study, various studies have shown better glycemic control and more tolerability with insulin analogs compared with human insulin in patients with T2DM [ 57 – 59 ]. Subsequently, cost-effectiveness of BIAsp 30 could be attributed to lower incidence of hypoglycemia in short-term and better prevention of DM related complications in long-term [ 60 , 61 ].…”
Section: Discussionsupporting
confidence: 82%
“…Our analysis showed that treating poorly controlled patients with BIAsp 30 is likely to be cost-saving and cost-effective in Iran. In parallel to the results of our study, various studies have shown better glycemic control and more tolerability with insulin analogs compared with human insulin in patients with T2DM [ 57 – 59 ]. Subsequently, cost-effectiveness of BIAsp 30 could be attributed to lower incidence of hypoglycemia in short-term and better prevention of DM related complications in long-term [ 60 , 61 ].…”
Section: Discussionsupporting
confidence: 82%
“…1a). Insulin analogues, B28Asp human insulin (insulin aspart) and B29Lys(ε-tetradecanoyl),desB30 human insulin (insulin detemir), also did not change survival rates significantly (electronic supplementary material [ESM] Table 1) [25]. However, human insulin could prevent the lifeshortening effect of HG conditions, increasing mean lifespan under HG conditions from 18.5 ± 0.3 to 20.4 ± 0.9 days ( p<0.05) and maximum lifespan from 25.8±0.3 to 29.7± 0.7 days ( p<0.01) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Insulin is an effective therapy to decrease the blood glucose levels in type 1 diabetes patients and is a selective therapy in type 2 diabetes patients 8 9 . A type of man-made insulin, protamine zinc insulin (PZI), has been accepted to enhance the medication safety of insulin 10 . However, exogenetic insulin may cause a strong rejection reaction and drug resistance, which restrains the use of insulin 11 .…”
mentioning
confidence: 99%